Pengoptimalam Omset UMKM Menggunakan Media Sosial dan Google Ad Sense - Wardhana, Ariyani; Sandiwarno, Sulis (ADI MASSI (JURNAL PENGABDIAN MASYARAKAT SISTEM INFORMASI), 2021)
Micro, Small and Medium Enterprises (MSMEs) are the business sector that contributes more than 99% of the total existing business actors. MSMEs are the type of business that is most immune to the monetary crisis and absorbs a lot of labor. However, some MSMEs are still not able to develop properly. This is due to a lack of commitment in running their business, lack of innovation, unable to reach the target market, and financing constraints. Food stalls, small workshops, kiosks, online shops for USNI students are among the less developed businesses. The use of social media and google ad sense is expected to be able to increase the ability of these SMEs to reach their target market with minimal costs, increase the creativity of business actors in marketing their products, and be able to continue to innovate following the trend of market competition. This community service activity was strongly supported by the USNI and the training process was held for one day by two instructors, followed by 18 representatives of MSMEs on the USNI campus, while the mentoring process for MSMEs in the environment around USNI was carried out for approximately two weeks. Keywords: face book, google ads, Instagram, social media, UMKM, USNI